Development of P4GN RPP (Prevention, Eradication, Misuse and Illicit Circulation of Drugs) Students as a Form of Defense for Millennial Young Generation at Islamic Universities of Kadiri - Aminah, Siti; Athori, Agus (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2019)
The state defense is the obligation of every citizen of Indonesia as stated in the Constitution of the year 1945 article 27 paragraph 3 that every citizen has the rights and obligation to participate in the efforts of the defense of the country. UNISKA as a higher education institution implements the Tri Darma Colleges in perspective of State Defense. Since UNISKA was declared as a Homeland Love campus based the Foundation decree No. 59/SK/YBCMP/IV/2017, UNISKA has given a course of state defense as compulsory of the institution for students semester 1. In one of the course materials is about the danger of drugs. Drugs at this time becomes a major threat to the millennial generation. So far, handling the drug is still loaded on the National Narcotics Agency (BNN). In the implementation still uses the model of lectures. It’s not effective yet because it isn’t systemic structured and massive. UNISKA as a higher education institution conducts research with the aim of developing a lesson plan of P4GN (Prevention, Eradication, Abuse, and Illegal drugs which are integrated with the course of the state defense. Through this course can be ensured the steps of handling the danger of drugs systemically, structurally and massively among the students who are part of the millennial generation. It’s hoped this course can be applied by all higher education institutions as a responsibility to participate in overcoming the danger of drugs. The design of this research is development research with the aim of producing a lesson plan of P4GN (Prevention, Eradication, Abuse, and Illegal drugs) for students of UNISKA. The stages of research are (1) conducting need survey (2) describing goal and objective (3) selecting the lesson plan (4) writing the lesson plan. The respondents in this research are the rector, 5 deans and the 7 heads of the program of study of UNISKA. The instruments in this study are questionnaires and documents. After having analyzed using the descriptive method it is found that all respondents support the existence of lesson plan of P4GN (Prevention, Eradication, Abuse, and Illegal drugs) to be applied in the lecture integrated with the course of state defense.